(untitled) (CIPEEX, 2024)
THE MEASURES ADOPTED TO CONTAIN THE SPREAD OF THE VIRUS, SUCH AS THE SUSPENSION OF VISITS AND OUTSIDE ACTIVITIES, HAVE EXACERBATED EXISTING PROBLEMS, SUCH AS SOCIAL ISOLATION AND ANXIETY AMONG INMATES. GIVEN THIS CONTEXT, IT IS POSSIBLE TO CONCLUDE THAT THE PANDEMIC HAS CRITICALLY EXPOSED THE STRUCTURAL AND MANAGEMENT DEFICIENCIES OF THE BRAZILIAN PRISON SYSTEM.